Identification with social role obligations, possible selves, and L2 motivation in foreign language learning. (July 2015) - Huang, Hung-Tzu; Hsu, Chun-Chieh; Chen, Shun-Wen
Abstract: This study discusses the motivational disposition of learners learning English as a second language (L2) and another third language (L3) simultaneously in Taiwan. Utilizing Dörnyei's (2005) L2 motivational self system as the framework for describing learner motivation and incorporating motivational characteristics specific to Confucian-influenced societies (Chen, Wang, Wei, Fwu, Hwang, 2009; Hwang, 2012 ), the present study investigates the predictive effects of learners' future L2 self-images and social identities on their L2 learning behaviors. A questionnaire with 35 Likert-type scale items was developed to survey the language learning motivation of 1132 college students who were taking English as an L2 and French, German, Japanese, or Korean as their L3 in Taiwan. Results from responses to the questionnaire show that Taiwanese language learners have unique motivation characteristics that are mediated by culturally and socially grounded self-identities. The study concludes that the foreign language learning of multiple languages within diverse local contexts provides insight to cross-cultural effects on the motivational properties of possible selves.